Topological optimization of 3D printed bone analog with PEKK for surgical mandibular reconstruction. (July 2020) - Cheng, Kang-jie; Liu, Yun-feng; Wang, Russell; Zhang, Jian-xing; Jiang, Xian-feng; Dong, Xing-tao; Xu, Xu
Abstract: Purpose: The purpose of this study was to analyze mechanical behaviors of a topologically optimized and 3D-printed mandibular bone block with polyetherketoneketone (PEKK) for surgical mandibular reconstruction. Materials and methods: 3D virtual mandibular models were reconstructed from cone beam computed tomography images. A proposed mandibular resection of the mandibular body (40 mm anterior-posteriorly) was segmented. Internal structure of the resected bone was designed with topological optimization. Dental implants and implant-supported crowns were integrated into the design. A second 3D virtual model was created with the same size and location of the defect but was reconstructed with a fibular graft and implant-supported crowns. The biomechanical behaviors of the two models were compared by finite element method (FEM) under the same boundary constraints and three loading locations, namely, central incisors, lower left and right side first molar areas. Results: The FEM results showed the maximum stresses and displacements of the topology optimized model were much lower than those of the model with fibular bone graft. The highest stress of the optimized mandibular model was located on the lower edge of the posterior border of bone analog, and fixation screws. The maximum displacement occurred at the lower edge of the proximal mandibular stump or the lower edge of the distal mandibular body on the contralateral site. Under the same three loading locations, the maximum stress of the optimized model significantly decreased by 67.9%, 71.9% and 68.6% compared to the fibular graft model. Conclusions: The 3D printed bone analog with topological optimization is patient-specific and has advantages over the conventional fibular bone graft for surgical mandibular reconstruction. The optimized PEKK bone analog model creates more normal stress-strain trajectories than the fibular graft model and likely provides better functional and cosmetic outcomes. Graphical abstract: Image 1 Highlights: A PEKK mandibular bone analog with complex structures was designed by topology optimization Integration of dental implants and zirconia crowns to the bone analog was important to mimic a clinical treatment. Exact shape, form and size of bone analog to replace resected bone has advantages over a grafted fibular bone. The PEKK mandibular bone analog model shows less stress under loadingscompared to a fibular graft bone model.